Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Use the elimination method to find all solutions of the system:

[tex]\[
\left\{
\begin{array}{l}
3x^2 - y^2 = 11 \\
x^2 + 4y^2 = 8
\end{array}
\right.
\][/tex]

The four solutions of the system are [tex]\((-a, -b)\)[/tex], [tex]\((-a, b)\)[/tex], [tex]\((a, -b)\)[/tex], and [tex]\((a, b)\)[/tex].

Using positive numbers, find:
[tex]\[
a = \quad \boxed{2} \quad \text{and} \quad b = \quad \boxed{}
\][/tex]


Sagot :

To find the solutions to the system of equations

[tex]\[ \begin{cases} 3 x^2 - y^2 = 11 \quad \text{(1)} \\ x^2 + 4 y^2 = 8 \quad \text{(2)} \end{cases} \][/tex]

we can use the elimination method step-by-step:

1. Multiply Equation (2) to facilitate elimination:
Multiply Equation (2) by 3 to match the coefficients of [tex]\( x^2 \)[/tex].

[tex]\[ 3(x^2 + 4y^2) = 3 \cdot 8 \][/tex]

Simplifying, we get:

[tex]\[ 3x^2 + 12y^2 = 24 \quad \text{(3)} \][/tex]

2. Subtract Equation (1) from Equation (3):
Subtract Equation (1) from Equation (3).

[tex]\[ (3x^2 + 12y^2) - (3x^2 - y^2) = 24 - 11 \][/tex]

Simplifying, we get:

[tex]\[ 3x^2 + 12y^2 - 3x^2 + y^2 = 13 \][/tex]

[tex]\[ 13y^2 = 13 \][/tex]

[tex]\[ y^2 = 1 \][/tex]

Therefore,

[tex]\[ y = \pm1 \][/tex]

3. Solve for [tex]\( x \)[/tex] when [tex]\( y = 1 \)[/tex] and [tex]\( y = -1 \)[/tex]:

- For [tex]\( y = 1 \)[/tex]:

Substitute [tex]\( y = 1 \)[/tex] into Equation (2):

[tex]\[ x^2 + 4(1)^2 = 8 \][/tex]

Simplifying, we get:

[tex]\[ x^2 + 4 = 8 \][/tex]

[tex]\[ x^2 = 4 \][/tex]

[tex]\[ x = \pm2 \][/tex]

- For [tex]\( y = -1 \)[/tex]:

Substitute [tex]\( y = -1 \)[/tex] into Equation (2):

[tex]\[ x^2 + 4(-1)^2 = 8 \][/tex]

Simplifying, we get:

[tex]\[ x^2 + 4 = 8 \][/tex]

[tex]\[ x^2 = 4 \][/tex]

[tex]\[ x = \pm2 \][/tex]

4. Find all solutions:

The solutions for the system are the pairs [tex]\((x, y)\)[/tex] which combine as:

[tex]\[ (2, 1), (-2, 1), (2, -1), (-2, -1) \][/tex]

5. Identify positive solutions:

From the solutions, we identify the positive solution for [tex]\( (a, b) \)[/tex]:

[tex]\[ a = 2, \quad b = 1 \][/tex]

6. Answer:

Therefore, the values for [tex]\( a \)[/tex] and [tex]\( b \)[/tex] are:

[tex]\[ a = 2 \quad \text{and} \quad b = 1 \][/tex]